Recording Policryps structures in photonic crystal fibers - Poudereux, David; Cano-García, Manuel; Alj, Domenico; Caputo, Roberto; Umeton, Cesare; Geday, Morten Andreas; Otón, José Manuel; Quintana, Xabier (Photonics Letters of Poland, 2017)
Policryps structures of photo-curable adhesive NOA61 and nematic liquid crystal mixture E7 have been created inside selected microchannels of photonic crystal fibers (PCF). The PCF was selectively infiltrated with the photopolymer-liquid crystal mixture for the writing of a holographic tunable grating inside specific holes of the photonic fiber. A 2um pitch grating was successfully recorded in the PCF inner holes with and without collapsing the fiber cladding. The liquid crystal is properly aligned in both cases. Full Text: PDF References Q. Liu, et al., "Tunable Fiber Polarization Filter by Filling Different Index Liquids and Gold Wire Into Photonic Crystal Fiber", J. Lightwave Technol. 34(10), 2484 (2016). CrossRef L. Velázquez-Ibarra, A. Díez, E. Silvestre, M.V. Andrés, "Wideband tuning of four-wave mixing in solid-core liquid-filled photonic crystal fibers", Opt. Lett. 41(11), 2600 (2016). CrossRef T. Larsen, A. Bjarklev, D. Hermann, J. Broeng, "Optical devices based on liquid crystal photonic bandgap fibres", Opt. Express 11(20), 2589 (2003). CrossRef H.Y. Choi, M.J. Kim, B.H. Lee, "All-fiber Mach-Zehnder type interferometers formed in photonic crystal fiber", Opt. Express 15(9), 5711 (2007). CrossRef D. Poudereux, P. Corredera, E. Otón, J.M. Otón, X.Q. Arregui, "Photonic liquid crystal fiber intermodal interferometer" Opt. Pura Apl. 46(4), 321 (2013). CrossRef T.R. Woliński, et al., "Tunable Optofluidic Polymer Photonic Liquid Crystal Fibers", Mol. Cryst. Liq. Cryst. 619(1), 2 (2015). CrossRef D. Budaszewski, T.R. Woliński, M.A. Geday, J.M. Otón, "Photonic Crystal Fibers infiltrated with Ferroelectric Liquid Crystals", Phot. Lett. Poland, 2(3), 110 (2010). CrossRef D. Alj, S. Paladugu, G. Volpe, R. Caputo, C. Umeton, "Polar POLICRYPS diffractive structures generate cylindrical vector beams", Appl. Phys. Lett., 107(20), 201101 (2015). CrossRef A. Veltri, R. Caputo, C. Umeton, A.V. Sukhov, "Model for the photoinduced formation of diffraction gratings in liquid-crystalline composite materials", Appl. Phys. Lett. 84(18), 3492 (2004). CrossRef T.J. Bunning, L.V. Natarajan, V.P. Tondiglia, R.L. Sutherland, "Holographic Polymer-Dispersed Liquid Crystals (H-PDLCs)", Annu. Rev. Mater. Sci. 30(1), 83 (2000). CrossRef R. Caputo, L. De Sio, A.V. Sukhov, A. Veltri, C. Umeton, "Development of a new kind of switchable holographic grating made of liquid-crystal films separated by slices of polymeric material", Opt. Lett., 29, 1261 (2004). CrossRef A. Marino, F. Vita, V. Tkachenko, R. Caputo, C. Umeton, A. Veltri, G. Abbate, "Dynamical behaviour of holographic gratings with a nematic film –Polymer slice sequence structure", Euro. Phys. J. E 15, 47 (2004). CrossRef G. Abbate, F. Vita, A. Marino, V. Tkachenko, S. Slussarenko, O. Sakhno, J. Stumpe, "New Generation of Holographic Gratings Based on Polymer-LC Composites: POLICRYPS and POLIPHEM", Mol. Cryst. Liq. Cryst. 453(1), 1 (2006). CrossRef G. Zito, S. Pissadakis, "Holographic polymer-dispersed liquid crystal Bragg grating integrated inside a solid core photonic crystal fiber", Opt. Lett. 38(17), 3253 (2013). CrossRef B. Sun, et al., "Unique Temperature Dependence of Selectively Liquid-Crystal-Filled Photonic Crystal Fibers", IEEE Phot. Technol. Lett. 28(12), 1282 (2016). CrossRef R. Caputo, et al., "POLICRYPS: a liquid crystal composed nano/microstructure with a wide range of optical and electro-optical applications", J. Opt. A: Pure Appl. Opt. 11(2), 024017 (2009). CrossRef J. Li, S.-T. Wu, S. Brugioni, R. Meucci, S. Faetti, "Infrared refractive indices of liquid crystals", J. Appl. Phys. 97(7), 073501 (2005). CrossRef